Study on Air Quality Index, Atmospheric Pollutants and Dry Deposition of PCDD/Fs in the Ambient Air near Southwest China - Xueyan Liu; Kangping Cui; Yen-Kung Hsieh; Ya-Fen Wang; Ruoxin Wang (Aerosol and Air Quality Research)
Abstract This study investigated the AQI (air quality index), atmospheric pollutants (PM2.5, NO2, and O3), and dry deposition of PCDD/Fs in Chengdu and Chongqing, near southwest China from 2020 to 2021. The results showed that the implementation of strict epidemic prevention action led to a significant improvement in the air quality in 2020. However, the air quality index increased again in 2021 as the economic activity was recovered. In February 2020, at the height of the epidemic, the monthly average PM2.5 and NO2 concentrations were estimated as 50.9 µg m–3 and 21.2 ppb, respectively in in Chengdu, and 48.9 µg m–3 and 22.9 ppb, respectively in Chongqing. In February 2021, when the economy was returned to normal, the monthly average PM2.5 and NO2 concentrations were 60.3 µg m–3 and 36.2 ppb respectively in Chengdu and 52.4 µg m–3 and 35.1 ppb, respectively in Chongqing. In addition, since O3 concentrations were influenced by the VOCs–NOx ratio, the reduction of NOx emissions and the increase of VOC emissions during the epidemic control period caused a change in the VOCs–NOx ratio, and thus leading to an increase in O3 concentrations. The monthly average concentration of O3 from March 2021 to May 2021 was significantly lower than that of 2020. Furthermore, the dry deposition flux of PCDD/Fs also changed in the period before and after the epidemic. The dry deposition flux of PCDD/Fs in 2021 was significantly higher than that of 2020, which was associated with the fuel consumption of various industrial plants. This study indeed provided useful information for the contribution of scientific communities and important data bank for the future air quality control.